2014
DOI: 10.1053/j.ackd.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Focal Segmental Glomerulosclerosis

Abstract: Focal segmental glomerulosclerosis (FSGS) is a histological pattern of injury on renal biopsy that can arise from a diverse range of causes and mechanisms. Although primary and secondary forms are described based on the underlying cause, there are many common factors that underlie the development of this segmental injury. In this review we will describe the currently accepted model for the pathogenesis of classic FSGS and review the data supporting this model. Although the podocyte is considered the major targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 58 publications
3
85
0
Order By: Relevance
“…Focal segmental glomerular sclerosis (FSGS) is a lesion of the kidney glomerulus that leads to nephrotic syndrome, typically progressing to end stage renal disease [Chen and Liapis, 2015; Jefferson and Shankland, 2014; Rood et al, 2012]. The key targets of this lesion are podocytes, highly specialized epithelial cells that enwrap the glomerular capillaries with highly elaborate foot processes [Jefferson and Shankland, 2014].…”
Section: The Role Of Inf2 In Human Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Focal segmental glomerular sclerosis (FSGS) is a lesion of the kidney glomerulus that leads to nephrotic syndrome, typically progressing to end stage renal disease [Chen and Liapis, 2015; Jefferson and Shankland, 2014; Rood et al, 2012]. The key targets of this lesion are podocytes, highly specialized epithelial cells that enwrap the glomerular capillaries with highly elaborate foot processes [Jefferson and Shankland, 2014].…”
Section: The Role Of Inf2 In Human Diseasementioning
confidence: 99%
“…The key targets of this lesion are podocytes, highly specialized epithelial cells that enwrap the glomerular capillaries with highly elaborate foot processes [Jefferson and Shankland, 2014]. Specialized cell-cell junctions between these foot processes, called slit diaphragms, serve as part of the kidney's filtration barrier.…”
Section: The Role Of Inf2 In Human Diseasementioning
confidence: 99%
“…There are different causes underlying the development of a FSGS pattern, and primary (idiopathic) FSGS has to be distinguished from secondary FSGS caused by known trigger. Regardless of the disease forms, the podocyte stands in the center of the disease and seems to be an important target in FSGS [5]. The pathomechanisms behind the different forms of FSGS disease appears to be similar, resulting in the same histological picture.…”
Section: Introduction: Overview Of Animal Models For Focal Segmental mentioning
confidence: 99%
“…Further studies revealed that enhanced AT 1 receptor signaling in podocytes leads to proteinuria and FSGS 23 , and inhibition of AT receptors is effective against proteinuria 24, 25 .…”
Section: Introductionmentioning
confidence: 99%